Development of Simple Additive Weighting (SAW) E-Module Learning Media Based on PJBL to Improve Learning Outcomes - Mufidah Nur Amaliah; Rangga Firdaus; Riswandi; Sheren Dwi Oktaria (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2025)
This study developed a Project-Based Learning (PJBL)-based Simple Additive Weighting (SAW) e-module to improve learning in the Decision Support System (DSS) course. The e-module was designed with structured material, multimedia, computational exercises, and case studies in line with PJBL syntax. Validation results show very high feasibility from subject matter experts (91.25%) and media experts (95%), while student response reached 91.33%. The effectiveness of the e-module is evident from the increase in student learning scores from 54.2 to 84.5 with an N-Gain of 0.66 and a Cohen's d score of 2.74, indicating a very large effect. These results show that the e-module is capable of improving conceptual understanding, analytical skills, and decision-making skills. This study contributes to the development of digital learning media and is limited to the scope of the pilot study. Further studies are recommended to involve a broader scope and more adaptive learning features.